2003
DOI: 10.1007/s00442-003-1425-y
|View full text |Cite
|
Sign up to set email alerts
|

Secondary succession is influenced by belowground insect herbivory on a productive site

Abstract: We investigated the effects of insect herbivory on a plant community of a productive old-field community by applying foliar and soil insecticides in a full factorial design. During the first 3 years of succession, insecticide treatments had only minor effects on total cover abundance and species richness. However, species ranking within the plant community was strongly affected by soil insecticide but not by foliar insecticide. Creeping thistle, Cirsium arvense, dominated the experimental plots with reduced ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 61 publications
1
57
1
Order By: Relevance
“…Aboveground and belowground biotic interactions vary with seasonal and successional time (Brown & Gange 1992;Schädler et al 2004;Bardgett et al 2005), as well as with latitudinal position (De Deyn & Van der Putten 2005). As fast growing plants are less well-defended by secondary chemistry than slowgrowing plants ( De Jong 1995), early succession plants in general are supposed to be less well directly defended to herbivores than late successional species (Price 1984).…”
Section: Biotic Interactions Modify Plant Species Abundancementioning
confidence: 99%
“…Aboveground and belowground biotic interactions vary with seasonal and successional time (Brown & Gange 1992;Schädler et al 2004;Bardgett et al 2005), as well as with latitudinal position (De Deyn & Van der Putten 2005). As fast growing plants are less well-defended by secondary chemistry than slowgrowing plants ( De Jong 1995), early succession plants in general are supposed to be less well directly defended to herbivores than late successional species (Price 1984).…”
Section: Biotic Interactions Modify Plant Species Abundancementioning
confidence: 99%
“…Based on the previously reported work in aboveground or belowground subsystems, we expected effects varying from additive to synergistic, or even antagonistic. As field experiments suggested different responses of plant community composition to aboveground and belowground plant enemies (Brown and Gange 1989, Scha¨dler et al 2004, Van Ruijven et al 2005, we expected that the strength of aboveground effects will not necessarily correlate with the strength of belowground effects. This may be due to defense responses in plants to aboveground herbivores differing from belowground herbivores, or root pathogens (Bezemer and Van Dam 2005, Kaplan et al 2008, Van Dam 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, most studies on aboveground-belowground interactions have focused on influences of aboveground and belowground herbivores, pathogens or mutualists on each other (e.g., Masters et al 1993, Bennett andBever 2007) or on interactions between aboveground herbivores and belowground decomposers (Bardgett and Wardle 2003). A number of studies have tested how aboveground and belowground herbivores may influence the composition of plant communities (Brown and Gange 1989, Scha¨dler et al 2004, Van Ruijven et al 2005. Few studies, however, have considered how plant exposure to both aboveground and belowground herbivores and pathogens may influence individual plants (Maron 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Such impacts, however, are due to a variety of mechanisms such as belowground herbivory (SCHÄDLER et al, 2004) and an acceleration of nutrient cycling via the action of arthropod detritivores (MASTERS, 2004;ENDLWEBER;SCHEU, 2007). SCHÄDLER et al (2004) concluded that insecticide-induced changes in plant community succession in a productive oldfield were partly due to the action of a phytophagous species damaging herb species.…”
Section: Discussionmentioning
confidence: 99%